Exhaled breath condensate in pediatric asthma: Promising new advance or pouring cold water on a lot of hot air? A systematic review1. Issue 5 (8th February 2013) - Thomas, P.S.; Lowe, A.J.; Samarasinghe, P.; Lodge, C.J.; Huang, Y.; Abramson, M.J.; Dharmage, S.C.; Jaffe, A.
Abstract Background Exhaled breath condensate (EBC) analysis is a simple non‐invasive technique that allows repeated collection of breath samples with a minimum of inconvenience for the subject. These breath samples can potentially indicate lung disease activity and given the ease of collection, EBC is becoming a useful research tool in the study of respiratory diseases. It has the potential to be used in both population‐based studies and in the context of pediatric asthma it may prove useful in diagnosis and monitoring. Methods A systematic review was conducted to identify studies of EBC markers in childhood asthma. Results Most of the studies were cross‐sectional in design, and the results suggest that simple chemical entities such as hydrogen ions (as pH), hydrogen peroxide, and oxides of nitrogen are associated with pediatric allergic asthma and exacerbations. In addition, more complex molecules including leukotrienes, prostaglandins, and cytokines such as the interleukins IL‐4 and IL‐5 are also elevated in the breath of those with asthma. Conclusion EBC has the potential to aid diagnosis, and to evaluate the inflammatory status of asthmatic children. Future studies may be able to refine further how best to collect EBC samples, to interpret them, and the technique has the potential to allow repeated sampling which will allow studies of natural history, pathogenesis and response to treatment to be undertaken. Pediatr Pulmonol. 2013; 48:419–442. © 2013 Wiley Periodicals, Inc.